Experimental Performance Of Humid Air Turbine Fueled By Biomass - Fauzi, Muhammad Fahmi Hasifi Md (Universiti Sains Malaysia, 2019)
The concern about environmental problems has led to more studies in alternative energy like renewable energy, biomass is one of them. As for electrical power generation, interest in small scale distributed generation (DG) has recently increased due to its advantages over centralized power generation. The externally fired gas turbine (EFGT) system is one of the main candidates for (DG) technology. With the hot air production in terms of combined heat and power (CHP) output of the (EFGT) system can generate electrical power generation. The injection of preheated water/steam in the (EFGT) system can increase the efficiency of the cycle. Therefore, the humid air turbine (HAT) cycle is used into the (EFGT) system. The purpose of this study is to characterize the performance of humid air turbine (HAT) fueled by biomass in the experimental method. With the (HAT) performance, can analyze the efficiency of the (HAT) cycle in generating (CHP). The combustion of each batch of 15kg biomass was fueled to characterize the performance of (HAT) cycle. The main findings showed that the maximum turbine inlet temperature (TIT) was 763°C at 0.2 bar. From the compressor and turbine power calculations, turbocharger efficiency was in the range of 8-12% and specific fuel consumption (SFC) ranging from 4 to 11 kg/kWh at different pressures. Besides, the steam injection was used to increase the humid air turbine (HAT) cycle by combustion of biomass in the boiler that attached to the (EFGT) system. Therefore, the experiment to characterize the performance of biomass boiler conducted to determine the best steam flow rate that will inject into the (EFGT) system. The main findings for experiment characterize biomass boiler are output and input power of biomass boiler, its efficiency and (SFC) at different steam flow rate. Boiler effeciency was in the range of 63-73% with average 0.21 kg/kWh.